Tobacco Taxation Influences the Smoking Habits of Adult Smokers Attending Smoking Cessation Clinic in Saudi Arabia - Altowiher, Najeeb Saud S.; Bustami, Rami; Alwadey, Ali M.; Alqahtani, Mansour (Frontiers in Public Health, 2022)
Objectives: To determine whether tobacco taxation has had a significant effect on the cessation of smoking by tracking the responses of participants. Methods: An interviewer-administered questionnaire of adult Saudi smokers and recent quitters attended cessation clinics between January 2018 and September 2019. Results: We interviewed 660 participants. The majority were men (98%) and residing western region (33%). Taxation had no effect on smoking for (58.6%), some effect for (33.3%), and substantial effect for (7.6%). Strategies adopted to cope with the taxation mainly were attempting to quit (68.6%) and cutting down (45.8%). Current smoking status was significantly associated with the impact of tobacco taxation. Meanwhile, Occupation, education (P = 0.03), and current smoking status (P = 0.07) were significantly associated with the impact of tobacco taxation. The strategies adopted in response to taxation were significantly associated with occupation (c2 = 30, degrees of freedom = 12, P < 0.001). Conclusions: Tobacco taxation was influential on 40% of the participants. Their attempts to opt for alternatives should be recognized for evaluating the policy to reduce adverse health impacts due to tobacco abuse.